PHYSICAL PARAMETERS OF 1-MCP TREATED APPLES AFTER EXPOSITION IN ROOM CONDITIONS AT THE END OF STORAGE - Melnyk, Oleksandr; Khudik, Liudmyla (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
Flesh firmness is reducing and background color is changing from green to yellow due to the chlorophyll degradation and synthesis of carotenoids and flavonoids during storage. These processes are accelerated more significantly at higher temperatures, so it is actuality to research the safety of products with post-harvest treatment of fruit apples with ethylene biosynthesis inhibitor 1-methylcyclopropene (1-MCP) at the end of sevenday’s exposure for 20±1 оС after refrigerated storage. Research objects were selected early–winter apple cultivars ‘Calville’ and ‘Spartan’, treated after harvest with 1–MCP (‘SmartFreshTM’ 0.068 g·m-3) for 24 h at 5±1 °C, after seven-day’s exposition at 20±1 оС in order to imitation the commodity turnover, at the end of storage for two, three, four, five and six months at 3±1 °C and relative humidity 85–90 % (non–treated fruits – control). The flesh firmness (kg/cm2) was determined from two opposite sides of each of the twenty apples by fixed on a tripod penetrometer FT 327 with plunger diameter 11 mm, previously cutting off the skin. The background color of the skin was evaluated by spektrokolorymetr «Specol» through the light reflection (%) at wave 675 nm that corresponds to the maximum of chlorophyll absorption in the place without surface color. The chlorophyll «a»+«b» content in the peel determined in alcohol extracts by spektrokolorymetr «Specol». Data are means of three replicates. It were fixed a significant slowdown the losses of flesh firmness and the skin background color of 1-MCP treated fruits of both early–winter apple cultivars at the end of exposition at 20±1 оС, compared to the control’s fruits. The level of light reflection from the skin of apples was increased and the chlorophyll content was decreased with increasing storage time. Close opposite correlations between these indicators were founded. Compared to 1-MCP treated apples, un-treated fruits of both cultivars were characterized by more intensive skin yellowing during storage due to the it faster decrease of chlorophyll «a»+«b» content and increase the light reflection level. Post-harvest treatment with 1-MCP is effective for restraining the ripening of early–winter apple cultivars at high temperature after refrigerated storage, providing higher on 1,1–1,3 points for the ‘Spartan’ and in 1,9–2 times – for ‘Calville’ that minimum 5,5 kg/sm2 consumer’s desirable level of flesh firmness and significantly better preservation of skin background color by the indicators of light reflection and chlorophyll content.